2010
DOI: 10.1063/1.3357344
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional doxorubicin/superparamagnetic iron oxide-encapsulated Pluronic F127 micelles used for chemotherapy/magnetic resonance imaging

Abstract: Polymeric micelles are frequently used to transport and deliver drugs throughout the body because they protect against degradation. Research on functional polymeric micelles for biomedical applications has generally shown that micelles have beneficial properties, such as specific functionality, enhanced specific tumor targeting, and stabilized nanostructures. The particular aim of this study was to synthesize and characterize multifunctional polymeric micelles for use in controlled drug delivery systems and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…These relaxitivity r 2 values were significantly larger than those for SPION-dextran NPs (30-50 Fe mM −1 S −1 ) [45] and Fe 3 O 4 -PEG-PAE (poly(b-amino ester) micelle (92.7mM −1 s −1 [46]). These r 2 values were also comparable to the values of reported SPION micelles:110.4 for folate-free SPION-DOX-micelles [31], 121.2 for PEG4.3k–PCL7.2k–SPION [36], 207.99 Pluoronic-F127-SPION micelles [37]. …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These relaxitivity r 2 values were significantly larger than those for SPION-dextran NPs (30-50 Fe mM −1 S −1 ) [45] and Fe 3 O 4 -PEG-PAE (poly(b-amino ester) micelle (92.7mM −1 s −1 [46]). These r 2 values were also comparable to the values of reported SPION micelles:110.4 for folate-free SPION-DOX-micelles [31], 121.2 for PEG4.3k–PCL7.2k–SPION [36], 207.99 Pluoronic-F127-SPION micelles [37]. …”
Section: Resultssupporting
confidence: 84%
“…The polymeric micelle has been widely studied as a novel nanomedicine platform for anticancer drug delivery and diagnostic imaging applications over the past decade [29-31, 35-37]. This nanoplatform was expected to prolong the drug circulation time in blood while reducing direct contact between drugs and healthy tissues or organs.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that daunorubicin loaded SPIONs increased the intracellular accumulation of drug in drug resistant leukemia cells, but their therapeutic advantage was unclear [22, 23]. These and other [2428] studies with drug loaded SPIONs demonstrate their advantage as drug delivery vehicles by increasing intracellular drug concentration and minimizing off-target side effects. However, no study to date has determined if drug loaded SPIONs are able to overcome MDR for improved treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In tumor-bearing mice, targeted NPs showed a higher tumor accumulation when compared with non-targeted NPs owing to the integrin-mediated endocytosis, which further led to enhanced tumor retardation. Studies using other polymers such as Pluronic® F-127 have also resulted in stable formulations capable of simultaneous imaging and therapy, suggesting that the strategy of encapsulating SPIO-DOX mixture to formulate nanotheranostic particles is applicable to many existing polymeric NP systems 66.…”
Section: Polymer-based Nanotheranosticsmentioning
confidence: 99%